Technical Guidance for The Development of The Basement Floor of Pos Paud Asparaga, Merjosari, Lowokwaru, Malang City - moch. chamim; Mohamad Zenurianto; Raden Ajeng Mariyana; Roland Gasenda Suryaningrat (Journal of Community Engagement, 2025)
Adequate physical facilities are essential to support safe, comfortable, and developmentally appropriate learning in Early Childhood Education (ECE). Pos PAUD Asparaga, a community-based ECE institution in Merjosari, Lowokwaru, Malang City, faces challenges related to deteriorating infrastructure and limited learning facilities. This community service activity aimed to provide technical guidance for improving the physical learning environment at Pos PAUD Asparaga. The program employed a technical assistance approach involving stakeholder coordination, needs assessment through field surveys and observations, preparation of working drawings, and participatory decision-making with teachers and community members. The results indicate that wall repair and learning space enhancement, including temporary aesthetic solutions, improved classroom appearance, comfort, and perceived safety. Although learning outcomes were not measured quantitatively, the improved environment is expected to support children’s engagement and well-being. This activity highlights the importance of integrating technical expertise with community participation in community-based ECE facility improvement.